Heir to the empire ebook - Zahn, Timothy (Star Wars: The Thrawn Trilogy, 2011)
#1 NEW YORK TIMES BESTSELLER • In this essential Star Wars Legends novel—the first ever to take place after the events of the original trilogy—Grand Admiral Thrawn makes his debut on the galactic stage. Five years ago, the Rebel Alliance destroyed the Death Star, defeated Darth Vader and the Emperor, and drove the remnants of the old Imperial Starfleet to a distant corner of the galaxy. Princess Leia and Han Solo are married and expecting twins. And Luke Skywalker has become the first in a long-awaited line of Jedi Knights. But thousands of light-years away, the last of the Emperor’s warlords, Grand Admiral Thrawn, has taken command of the shattered Imperial fleet, readied it for war, and pointed it at the fragile heart of the New Republic. For this dark warrior has made a vital discovery that could destroy everything the courageous men and women of the Rebel Alliance fought so hard to build.